Brushwood fishing in Longos, San Fabian, Pangasinan with notes on some aspects of fish sheltering behavior - Distor, Ma. Consuelo C. (University of the Philippines in the Visayas, 1988)
Brushwood fishing was describe and the effectiveness of brushwood fishing shelters in luringand aggregating fish was assessed in terms of catch composition, catch per unit effort and some aspects of fish sheltering behavior. Ten genera of fish, shrimp and crab were noted to occur within fish shelters during the study on the brushwood fishery in Longos, San Fabian, Pangasinan conducted from January to June, 1986. The total catch consisted mostly of Penaeus spp. (40.4%), Scylla serrate (11.2%), Lutjanus spp. (8.7%), Singanus spp. (8.2%), Mugilwas chosen for the study and observation on aspects of fish sheltering behavior due to its economic importance. Data collected on the occurrence of Siganusvermiculatus within the fish shelters suggested that fry and sexually mature fish tend to seek shelter among the brush pile more than the immature fish of the species. Sixty-six percent of the total catch of the species was composed of fry while the remaining constituted 12% of mature females in the size range of 11.2-13.0 cm (TL), 10% mature males measuring 11.0-12.0 cm (TL), and 12% of immature fishes measuring 9.0-10.0 cm (TL).